Curriculum changes in the Visegrad Four: three decades after the fall of communism Studies from Hungary, Poland, the Czech and Slovak Republics - Janík, Tomáš; Porubský, Štefan; Chrappán, Magdolna; Kuszak, Kinga (Waxmann, 2020)
School systems in the Visegrad Four countries have gone through significant change since the political upheavals of 1989. The book describes developments in curriculum and curriculum policy over the last three decades and considers the possible impact and perspectives of current changes. It explores the nature of curriculum reform, addresses the challenge of its implementation and highlights the reform as a means by which school quality can be improved and as a 'provider' of aims and contents of school education. Hopefully, the book will contribute to the discussion of options for further curriculum development and curriculum policy in the Visegrad Four and other countries with a similar educational background
Keywords: Allgemeine Erziehungswissenschaft; Curriculum changes; Czech; Historische Bildungsforschung; Hungary; Neuzeit & Zeitgeschichte; Poland; Slovak Republics; Studie; study; Visegrad Four